Assessment of the analytical performances and sample stability on ST Genesia system using the STG‐DrugScreen application. (31st May 2019) - Douxfils, Jonathan; Morimont, Laure; Bouvy, Céline; de Saint‐Hubert, Marie; Devalet, Bérangère; Devroye, Célia; Dincq, Anne‐Sophie; Dogné, Jean‐Michel; Guldenpfennig, Maïté; Baudar, Justine; Larock, Anne‐Sophie; Lessire, Sarah; et al.
Abstract: Background: Thrombin generation testing has been used to provide information on the coagulation phenotype of patients. The most used technique is the calibrated automated thrombogram (CAT) but it suffers from a lack of standardization, preventing its implementation in routine. The ST Genesia is a new analyzer designed to assess thrombin generation based on the same principle as the CAT. Unlike the CAT system, the ST Genesia is a benchtop, fully automated analyzer, able to perform the analyses individually and not by batch, with strict control of variables such as temperature and volumes, ensuring, theoretically, maximal reproducibility. Objectives: This study aimed at assessing the performance of the STG‐DrugScreen application on the ST Genesia analyzer. We also aimed at exploring stability of plasma samples after freezing and defining a reference normal range. Results: Results demonstrated the excellent interexperiment precision of the ST Genesia and confirmed that the use of a reference plasma helps reducing the inter‐experiments variability. Stability revealed that plasma samples are stable for at least 11 months at −70°C or lower, except for those containing low molecular weight heparins which have to be tested within 6 months. Freezing had no effect on the majority of thrombin generation parameters except on time to peak. Conclusions: Our results suggest an easy implementation of thrombin generation with the use of ST Genesia in the routine laboratory. This will facilitate the design of multicentric studies and enable the establishment of reliable and evidence‐based thresholds, which may improve the management of patients treated with anticoagulants.